Kajian Identifikasi Daya Tampung Beban Pencemaran Kali Ngrowodengan Menggunakan Paket Program Qual2kw - Fatmawati, Reni; Masrevaniah, Aniek; Solichin, M. (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Ngrowo river is a tributary of Brantas river that located in Tulungagung Regency, East Java Province. Ngrowo river has function as a drainage channel not only from urban area but also from agricultural. The research objectives were determine of pollutionloadsfrom tributaries as apointsource, analyze of water pollution load and apply of Qual2Kwmodel to determine of the maximumpollution load on Ngrowo River.Primary data conducted with collected water sample at each segment that it representation of sources of water pollution. The water pollution sources on study area from domestic, agricultural and industrial. Water parameter was analysis such as DO(Dissolved Oxygen), BOD(Biochemichal OxygenDemand), and NO3(nitrate). Secondary data such as waterqualitymonitoring dataand discharge, and climatologicalobtained from theInstitutionaccording toauthorities.The analysisofpollution load capacityusingQUAL2Kwmodel that is method was recommended by on Regulation of the Minister of EnvironmentNo.01of 2010 onWaterPollution ControlProcedure). Based on results simulation that at all reach Ngrowo River the pollution load (BOD parameter) already exceed of class II and class III of water quality standard. The results showNgrowo River has capacity load of BOD and NO3 in wet season on class III water quality standard. Ngrowo River as North Part, the capacity of the BOD is equal to 6.634,59 kg / day and NO3 by 30.015,23 kg /day. Meanwhile at Ngrowo River South Part, the capacity of the BOD is equal to 3.007,25 kg / day and NO3 at 21.098,90 kg / day.Key words: pollution load, Qual2Kw Model, water quality